Помогите решить пожалуйста.

(x+3)/(x-3) + (x-3)/(x+3) - 10/3 = 0

(5x+7)/(x-2) - (2x+21)/(x+2) - 26/3 = 0

 x^{3} - 2x - 4 = 0

1

Ответы и объяснения

2013-09-30T14:06:40+00:00
1)  ( 3(x+3)(x+3) + 3(x-3)(x-3) - 10(x^2 - 9) ) / 3(x-3)(x+3) = 0

     ( 3(2x^2 + 18) - 10x^2 +90 ) / 3(x-3)(x+3) = 0
        
      4x^2 - 144 = 0
      3(x-3)(x+3) не равно 0     x не равно 3 , x не равно -3
    
    (2x - 12)(2x + 12) =0

  2x - 12 = 0    или   2x + 12 = 0
   x = 6                        x = -6
Ответ: x = 6, x = -6  

2) ( (5x+7)*3*(x+2) - (2x+21)*3*(x-2) - 26*(x^2 - 4) ) / 3(x-2)(x+2) = 0

( 9x^2 + 168 - 26x^2 + 104) / 3(x-2)(x+2) = 0
17x^2 - 272 = 0
3(x-2)(x+2) не равно 0 x не равен -2 ; x не равен 2
17( x^2 - 16) = 0
(x - 4)( x+4) = 0
x = 4 x = -4
Ответ: х = 4, х = -4